Study on how to remove IOE to LAMP of IT architecture of the telecom enterprise - Man LI; Wensheng YAO (Dianxin kexue)
The different localization and the different application scenarios between IOE and LAMP architecture were introduced. IT current situation and the driving force of removing IOE in telecom enterprise were analyzed. The differences of the business model，service characteristics and IT localization between the traditional telecom enterprises and the internet companies were studied. The overall implementation strategy of removing IOE and the suitable business scenario were proposed，and the effect of removing IOE from the billing system was expounded.